2019
DOI: 10.1200/jco.2019.37.15_suppl.101
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker analyses from JAVELIN Renal 101: Avelumab + axitinib (A+Ax) versus sunitinib (S) in advanced renal cell carcinoma (aRCC).

Abstract: 101 Background: The phase 3 JAVELIN Renal 101 trial in previously untreated patients (pts) with aRCC demonstrated a progression-free survival (PFS) benefit and higher objective response rate with A+Ax vs S (Motzer, ESMO 2018; LBA6_PR). Here, we report outcomes from biomarker analyses of baseline tumor samples. Methods: We correlated efficacy with the results of molecular analyses of tissue samples from all 886 pts enrolled in JAVELIN Renal 101. Nephrectomy or tumor samples were characterized by immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 0 publications
7
66
0
1
Order By: Relevance
“…This finding was confirmed when this gene signature was prospectively tested in the 823 patients in the IMmotion 151 study [69]. Moreover, similar results from biomarker analyses of 886 tumor samples of the JAVELIN Renal 101 study (avelumab/axitinib vs. sunitinib) were recently presented by Choueiri et al [70]. It was demonstrated that high expression of the angiogenesis gene signature was associated with a longer PFS when treated with sunitinib and a low expression improved PFS in the avelumab/axitinib arm.…”
Section: Molecular Correlates Of Clinical Outcome To Icisupporting
confidence: 65%
“…This finding was confirmed when this gene signature was prospectively tested in the 823 patients in the IMmotion 151 study [69]. Moreover, similar results from biomarker analyses of 886 tumor samples of the JAVELIN Renal 101 study (avelumab/axitinib vs. sunitinib) were recently presented by Choueiri et al [70]. It was demonstrated that high expression of the angiogenesis gene signature was associated with a longer PFS when treated with sunitinib and a low expression improved PFS in the avelumab/axitinib arm.…”
Section: Molecular Correlates Of Clinical Outcome To Icisupporting
confidence: 65%
“…However, in RCC, tumor-infiltrating lymphocyte (TIL) abundance is inversely correlated with survival (11)(12)(13). Biomarker analysis from recent clinical trials comparing PD-1 blockade versus anti-angiogenic inhibitors and combination therapies in treatment-naïve ccRCC patients also demonstrated the inverse relationship between T cell infiltration and clinical outcomes (14,15). Other abundant immune players in the ccRCC TME include monocytes, dendritic cells, and tumor-associated macrophages (16), which are now being harnessed for discovery of novel gene programs but remain far less studied than T cells.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that RNA‐based signatures interrogating angiogenesis and specific inflammatory conditions, such as upregulation of interferon‐gamma signaling, were associated with prolonged progression‐free survival under combinatorial therapy with sunitinib and atezolizumab 14 . Pointing in a similar direction, an exploratory analysis of the JAVELIN 101 trial suggested that focused gene expression profiling might identify patients who benefit the most from these novel combinatorial therapies 15 . Implementation of such biomarkers in a routine diagnostic setting requires the use of specific assays that are able to robustly interrogate formalin‐fixed and paraffin‐embedded (FFPE) clear cell renal cell carcinoma (ccRCC) samples but comparative studies analyzing technical aspects of different high throughput platforms are lacking.…”
Section: Introductionmentioning
confidence: 99%